Absolute Configuration and Antileishmanial Activity of (–)-Cyclocolorenone Isolated from Duguetia lanceolata (Annonaceae) - Monteiro, Jackson; Passero, Luiz Felipe D. [UNESP]; Jesus, Jéssica A.; Laurenti, Márcia D.; Lago, João H. G.; Soares, Marisi G.; Batista, Andrea N. L.; Batista, João M.; Sartorelli, Patricia (Bentham Science Publishers, 2022)
Background: The fractionation of the n-hexane phase of the EtOH extract from the leaves of Duguetia lanceolata (Annonaceae) led to the identification of the sesquiterpene (–)-cyclocolorenone. Objectives: Chemical characterization, including determination of the absolute stereochemistry, and in vitro evaluation of antileishmanial activity of the sesquiterpene (–)-cyclocolorenone, isolated from D. lanceolata, were carried out. Methods: (–)-Cyclocolorenone was isolated from D. lanceolata leaves using different chromato-graphic steps and its structure was defined by analysis of NMR and ESI-HRMS data. Additionally, the absolute configuration of (–)-cyclocolorenone was ambiguously assigned by means of vibrational circular dichroism (VCD). Antileishmanial activity of (–)-cyclocolorenone was evaluated on promastigote and amastigote forms of Leishmania (Leishmania) amazonensis. The integrity of the cell membrane of L. (L.) amazonensis was analyzed using the SYTOX green probe. Results: (–)-(1R,6S,7R,10R)-Cyclocolorenone displayed activity against promastigotes and amastigotes forms of L. (L.) amazonensis with IC50 of 4.54 and 28.44 μM, respectively. Furthermore, this compound was non-toxic in J774 macrophage cells (CC50 > 458.71 μM) with a selectivity index > 100 (promastigotes) and > 32.2 (amastigotes). Additionally, (–)-cyclocolorenone was observed to target the parasite cell membrane. Conclusion: Obtained data suggested that (–)-cyclocolorenone, in which absolute configuration was determined, can be considered as a scaffold for the development of new drugs for the treatment of leishmaniasis.
Keywords: (–)-Cyclocolorenone; Antileishmanial activity; Cell membrane; Duguetia lanceolata; Macrophage cells; VCD